The Implementation of Diversion for Juvenile Offenders: A Case Study in the Batu City Police Department - Kurniawan, Rudi Eko; Sunardi, Sunardi; Muhibbin, Moh. (Dinasti Research, 2025)
The juvenile justice system is closely related to the diversion approach as a form of settlement effort for children in conflict with the law. Diversion in this case is a legal effort in resolving cases so that children in conflict with the law can avoid the consequences of judicial procedures which will have a direct impact on the child's psychological and mental state. Based on observations that have been made, in 2024 there have been at least 10 cases of criminal acts involving children as perpetrators in the jurisdiction. The perpetrators of the persecution are known to be 13 years old and in grade 7 of Junior High School (SMP). Diversion as an alternative approach in handling criminal offenses has been seen as an appropriate step to prosecute and guarantee the rights of children in conflict with the law. This research is empirical juridical research using sociological approach and statutory approach. The data used in this research consists of primary data sourced from the results of interviews and observations, as well as secondary data sourced from legal materials in the form of regulations and legislation relevant to the research topic. Data analysis is carried out qualitatively to describe and analyze the application of diversion to juvenile offenders in the Batu Resort Police. The results showed that diversion has not been realized comprehensively in the Batu City Resort Police. The police tend to prefer to use a restorative justice approach rather than diversion because the circumstances in the field do not allow for the application of diversion. Factors that hinder the implementation of diversion in the Batu City Resort Police include individual, procedural, and technical factors. Concrete efforts that have been made by the PPA unit of the Batu City Resort Police to overcome obstacles in the implementation of diversion include the formation of the PPA Task Force in collaboration with various other agencies, such as the Batu City District Attorney's Office, the Batu City Social Service, the Batu City Office of Women's Empowerment, Child Protection and Population Control and Family Planning (DP3AP2KB), the Batu City Education Office, and the Batu City Religious Ministry to socialize the improvement of child protection